Development of humanized culture medium with plant-derived serum replacement for human pluripotent stem cells - Kunova, Michaela; Matulka, Kamil; Eiselleova, Livia; Trckova, Petra; Hampl, Ales; Dvorak, Petr (Reproductive biomedicine online, 2010)
For human embryonic stem cells (ESC) to be used in cell replacement therapies, they must be grown under good manufacturing conditions in a chemically defined medium that lacks animal proteins. This study examined the ability of a newly designed medium containing the plant-derived serum replacement VegetaCell and other reagents of human origin to support undifferentiated growth and pluripotency of human ESC. This medium was tested in several culture systems, using human fibroblasts as a feeder layer or Matrigel in a feeder-free culture. Even under the most stringent feeder-free conditions without conditioned medium, human ESC exhibited an undifferentiated morphology, expressed markers of undifferentiated cells, demonstrated high alkaline phosphatase activity and multilineage differentiation and retained a normal karyotype. Compared with human ESC grown in standard culture conditions, human ESC maintained in humanized VegetaCell medium show longer cell cycles and decreased cell death. The availability of an animal protein-free medium supplemented with the low-cost VegetaCell reagent expands the repertoire of media for culturing human ESC as well as induced pluripotent stem cells for drug testing and cell replacement therapy.
Keywords: kolagen; laminin; Culture Media; Cell Cycle; apoptóza; Cell Differentiation; Cell Culture Techniques; pluripotentní kmenové buňky; Collagen; indukované pluripotentní kmenové buňky; proteoglykany; Cell Proliferation; Drug Combinations; fixní kombinace léků; Embryonic Stem Cells; Proteoglycans; buněčný cyklus; Culture Media, Serum-Free; embryonální kmenové buňky; Humans; Laminin; Pluripotent Stem Cells; Fibroblasts; kultivační média; Induced Pluripotent Stem Cells; proliferace buněk; buněčné kultury; Apoptosis; buněčná diferenciace; kultivační média speciální; Culture Media, Conditioned; lidé; fibroblasty; kultivační média bez séra